2018
DOI: 10.1016/j.neunet.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

An optimal control strategy for hybrid actuator systems: Application to an artificial muscle with electric motor assist

Abstract: Humans use multiple muscles to generate such joint movements as an elbow motion. With multiple lightweight and compliant actuators, joint movements can also be efficiently generated. Similarly, robots can use multiple actuators to efficiently generate a one degree of freedom movement. For this movement, the desired joint torque must be properly distributed to each actuator. One approach to cope with this torque distribution problem is an optimal control method. However, solving the optimal control problem at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…It was found that fatigue of forearm muscles developed when the subject continued to control the nger position with EMG signals of the muscles. An optimal control strategy for a pneumatic rubber actuator (the static actuator) has been developed for an assistive robot [21]. A control strategy both for the static and astatic actuators for an actual articial muscle is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that fatigue of forearm muscles developed when the subject continued to control the nger position with EMG signals of the muscles. An optimal control strategy for a pneumatic rubber actuator (the static actuator) has been developed for an assistive robot [21]. A control strategy both for the static and astatic actuators for an actual articial muscle is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…However, just compensation is not enough for a dynamic swing. In another study, an optimal control strategy in which a different bandwidth between pneumatic and electric control was proposed [20]. An optimal control method may be suitable for dynamic swing motion.…”
Section: B Hybrid Controlmentioning
confidence: 99%
“…Since the introduction of the HPEA idea in 1987 [4], different designs have been proposed to develop this type of actuator. They include a combination of a DC motor and a rotary pneumatic motor 2 of 15 in parallel [5], pneumatic muscle actuators (PMA) with a DC motor [2,[6][7][8], pneumatic cylinders with a DC motor [9,10], and a pneumatic cylinder integrated within a linear motor [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been some papers focused on position controller design for HPEAs [3,6,10], very few have used a controller that incorporates each actuator's characteristics and studied the allocation problem alongside the position control problem. In [7], an optimization method is proposed for the torque allocation of a HPEA consisting of a PMA and an electric motor. They proposed a two-stage optimization approach that can be used for redundant actuators that consist of a higher bandwidth actuator and a lower bandwidth one.…”
Section: Introductionmentioning
confidence: 99%